An Examination of TikTok's Impact on Indonesian Digital Marketing Trends - Ependi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
The function of TikTok as a digital marketing platform and its impact on contemporary marketing trends in Indonesia are investigated in this study. TikTok, one of the social media sites with the highest rate of growth in the world, has grown to be an important tool for companies looking to communicate with customers through original and engaging content. The purpose of this study is to examine how TikTok influences the development of digital marketing tactics, particularly in small and medium-sized businesses (SMEs), large corporations, and content creators in Indonesia. Through a qualitative and quantitative approach, data were collected from surveys, case studies, and secondary sources to identify how well TikTok campaigns work to increase brand recognition and change consumer behavior, and driving sales. The findings indicate that TikTok's algorithm, short video format, and extensive user base have transformed traditional marketing approaches, enabling brands to connect with younger demographics, particularly Generation Z and Millennials. However, challenges such as content saturation, maintaining engagement, and competition among brands remain significant. This study highlights TikTok's growing potential in shaping Indonesia's digital marketing landscape and provides information to help advertisers improve their tactics on the platform.